PENETAPAN KADAR FLAVONOID TOTAL EKSTRAK DAUN CENGKEH (Syzygium aromaticum (L.) Merr & Perry) - Wahyulianingsih Wahyulianingsih; Selpida Handayani; Abd. Malik (Faculty of Pharmacy, Universitas Muslim Indonesia, 2016)
Clove (Syzygium aromaticum (L.) Merr & Perry) is one of the plants used as medicine, society used leaves as anti-inflammatory drugs at the time of toothache, which at the leaf contained flavonoids. The aim of this study is to determine the content of total flavonoid of ethanol extract clove leaf (EECL). Clove leaf was extracted using maceration method with ethanol as a solvent during at 3 x 24 hours. Analysis qualitative of flavonoids compound using thin layer chromatography method. Determination of total flavonoids content of clove leaves using spectrophotometri UV-Vis method λ 418 nm. The result of the research with rendamen yield of EECL were 16,1134%, and total flavonoids content is 73,08 mgRE/g extract with persentation 7,308%.